The Effect of Large Companies on Spatial Structure in Central and Eastern Europe with a Particular Focus on Enterprises in the Technology, Media & Telecommunications Industry - Nagy, Zoltán; Tóth, Géza (Theory, Methodology, Practice – Review of Business and Management, 2019)
Many theoretical and practical works aim at describing the spatial structure of Central and Eastern Europe. This article gives an overview of papers describing the spatial structure of Central and Eastern Europe with different methods. Our goal is to contribute to understanding the Central and Eastern European economic spatial structure and within this we examine the role of the Technology, Media & Telecommunications (TM&T) industry. This industry was chosen because it includes the most knowledge-intensive enterprises. We found that this industry plays a small role in the activities of the most important companies in the region. The capital’s major economic centres are the capitals. Thus, both the Central European Pentagon and the New Banana spatial models are suitable for describing the spatial structure. The spatial picture of the TM&T industry is basically concentrated on relatively few large cities, and the region’s most important centre is Warsaw.